2019
DOI: 10.1007/978-3-030-28954-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reverse-Engineering Black-Box Neural Networks

Abstract: Many deployed learned models are black boxes: given input, returns output. Internal information about the model, such as the architecture, optimisation procedure, or training data, is not disclosed explicitly as it might contain proprietary information or make the system more vulnerable. This work shows that such attributes of neural networks can be exposed from a sequence of queries. This has multiple implications. On the one hand, our work exposes the vulnerability of black-box neural networks to different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 20 publications
2
133
0
Order By: Relevance
“…We further assume that the shadow model uses the same ML algorithm and has the same hyperparameters as the target model. To achieve this in practice, the adversary can either rely on the same MLaaS provider which builds the target model or perform model extraction to approximate the target model [43], [30], [45]. Later in this section, we show this assumption can be relaxed as well.…”
Section: A Threat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We further assume that the shadow model uses the same ML algorithm and has the same hyperparameters as the target model. To achieve this in practice, the adversary can either rely on the same MLaaS provider which builds the target model or perform model extraction to approximate the target model [43], [30], [45]. Later in this section, we show this assumption can be relaxed as well.…”
Section: A Threat Modelmentioning
confidence: 99%
“…Despite being popular, ML models are vulnerable to various security and privacy attacks, such as model inversion [12], adversarial examples [15], and model extraction [43], [30], [45]. In this paper, we concentrate on one such attack, namely membership inference attack.…”
Section: Introductionmentioning
confidence: 99%
“…However, for more complex models such as neural networks, the attacker cannot simply solve nonlinear equations to arrive at model weights, but must instead train a 'student' network on inputoutput pairs collected from the API [31]. A similar work [32] shows the simplicity of reverse-engineering black-box neural network weights, architecture, optimization method and the training/data split. In [33], authors reframe the goal from model theft, to arriving at a 'knockoff' model exhibiting the same functionality.…”
Section: Attacks On Deployed Neural Networkmentioning
confidence: 99%
“…In order to violate the integrity of a machine learning model, attackers may attempt to find adversarial examples [35]. While most attacks rely on having access to the white-box model or the output gradient, several works have shown that even black-box networks [32] and networks with obfuscated gradients [36] are not resistant to determined attackers.…”
Section: Attacks On Deployed Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation